Jabiyeva, Telli - (:unkn) unknown (My University, 2026)
Telli Elshad gizi Jabiyeva graduated from the Azerbaijan University of Architecture and Construction (AzUAC) in 2013 with a Bachelor’s degree in Geodesy and Cartography Engineering. She subsequently obtained a Master’s degree with honors in Land Development, Land and Urban Cadastre from Azerbaijan State Agrarian University in 2016. She began her professional career in 2013 as a Technician at the Bakumetrolayiha Institute of Baku Metro CJSC. From 2015 to 2018, she held managerial positions at Geosurvey LLC and Astuğ Yapı’s Azerbaijan branch, gaining experience in international engineering and geodetic projects. Since 2019, she has been working at AzUAC, initially as a Senior Laboratory Assistant and, since 2023, as an Assistant at the Department of Geomatics. Telli Jabiyeva is the author of 38 scientific and academic works, including 20 scientific articles, 15 conference papers and theses, 2 methodological materials, and 1 collection of course programmes. Her research interests include satellite geodetic measurements, Geographic Information Systems (GIS), modern surveying technologies, land management and cadastral digitization, remote sensing, and aerial photography data processing.